Implementasi Media Pembelajaran Fisika Berupa Tabung Viskositas Dengan Analisis Video Menggunakan Software Tracker - Putra, Bayu Eka (Jurnal Pendidikan Fisika dan Sains (JPFS), 2022)
This study aims to determine student responses from the implementation of physics learning media in the form of viscosity tubes with video analysis using tracker software. In the preliminary study that has been done previously, the authors found several problems including students feeling that physics is difficult, too many formulas, and boring. In addition, students also have not been able to apply the knowledge that has been obtained at school in everyday life related to physics material. The causal factors that occur in schools related to the achievement of understanding essential physics concepts that have not been optimally mastered by students in learning include: less interactive learning media, incomplete experimental kits, and lack of student motivation. The research method used is Research & Development. The sampling technique of this research is purposive sampling. The instrument used was a questionnaire containing eight statements with a score range of 1 to 5 on a Likert scale. The research results obtained are the use of viscosity tube media and video analysis using tracker software, students can easily understand the material and make learning more fun.